Dietary supplementation with fiber, "biotics, " and spray-dried plasma affects apparent total tract macronutrient digestibility and the fecal characteristics, fecal microbiota, and immune function of adult dogs. (18th February 2022) - Lee, Anne H; Lin, Ching-Yen; Do, Sungho; Oba, Patricia M; Belchik, Sara E; Steelman, Andrew J; Schauwecker, Amy; Swanson, Kelly S
Abstract: A variety of functional ingredients, including fibers, prebiotics, probiotics, and postbiotics may be added to pet foods to support gastrointestinal and immune health. While many of these ingredients have been tested individually, commercial foods often include blends that also require testing. This study was conducted to evaluate the effects of diets containing blends of fibers, "biotics, " and/or spray-dried plasma on apparent total tract digestibility (ATTD ), stool quality, fecal microbiota and metabolites, and immune health outcomes of adult dogs. A total of 12 healthy adult intact English pointer dogs (6 M, 6 F; age = 6.4 ± 2.0 yr; BW = 25.8 ± 2.6 kg) were used in a replicated 3 × 3 Latin square design to test diets formulated to: 1) contain a low concentration of fermentative substances (control diet, CT ); 2) be enriched with a fiber–prebiotic–probiotic blend (FPPB ); and 3) be enriched with a fiber–prebiotic–probiotic blend + immune-modulating ingredients (iFFPB ). In each 28-d period, 22 d of diet adaptation was followed by a 5-d fecal collection phase and 1 d for blood sample collection. All data were analyzed using SAS 9.4, with significance being P < 0.05 and trends being P < 0.10. FPPB and iFPPB diets led to shifts in numerous outcome measures. Dry matter (DM ), organic matter, fat, fiber, and energy ATTD were lower ( P < 0.01), fecal scores were lower ( P < 0.01; firmer stools), and fecal DM% was higher ( P < 0.0001) in dogs fed FPPB or iFPPB than those fed CT. Serum triglycerides and cholesterol were lower ( P < 0.01) in dogs fed FPPB or iFPPB than those fed CT. Fecal protein catabolites (isobutyrate, isovalerate, indole, and ammonia) and butyrate were lower ( P < 0.05), while fecal immunoglobulin A (IgA ) was higher ( P < 0.01) in dogs fed FPPB and iFPPB than those fed CT. Fecal microbiota populations were affected by diet, with alpha-diversity being lower ( P < 0.05) in dogs fed iFPPB and the relative abundance of 20 bacterial genera being altered in dogs fed FPPB or iFPPB compared with CT. The circulating helper T cell:cytotoxic T cell ratio was higher ( P < 0.05) in dogs fed iFPPB than those fed CT. Circulating B cells were lower ( P < 0.05) in dogs fed FPPB than those fed iFPPB, and lower ( P < 0.05) in dogs fed iFPPB than those fed CT. Our results demonstrate that feeding a fiber–prebiotic–probiotic blend may provide many benefits to canine health, including improved stool quality, beneficial shifts to fecal microbiota and metabolite profiles, reduced blood lipids, and increased fecal IgA. Lay Summary: A variety of functional ingredients—those that provide benefits beyond their nutritional value—may be added to pet foods to support gastrointestinal and immune health. While many of these ingredients have been tested individually, commercial foods often include blends that also require testing. This study was conducted to evaluate the effects of diets containing blends of dietary fibers and other functional ingredients on nutrient digestibility and the stool characteristics and immune health outcomes of adult dogs consuming them. Treatments included a control diet containing low amounts of dietary fiber, a diet containing a fiber–prebiotic–probiotic blend, and a diet containing the fiber–prebiotic–probiotic blend as well as immune-modulating ingredients. The test diets were shown to shift many outcome measures. First, they were shown to reduce nutrient digestibility and decrease fecal scores (more firm stool). Second, test diets reduced blood lipids and beneficially altered fecal metabolite concentrations. Third, test diets increased fecal immunoglobulin A concentrations, suggesting enhanced gut immunity. Lastly, the test diets shifted fecal bacterial populations. Our results demonstrate that feeding a fiber–prebiotic–probiotic blend may provide many benefits to canine health, including improved stool quality, beneficial shifts to fecal bacteria and metabolite profiles, reduced blood lipids, and enhanced gut immunity. Abstract : This study demonstrates that feeding a diet containing a fiber–prebiotic–probiotic blend to adult dogs may provide many health benefits, including improved stool quality, beneficial shifts to fecal bacteria and metabolite profiles, reduced blood lipids, and enhanced gut immunity.